Is conservative approach a better option for primary treatment of closed tibia fractures in Albers- Schonberg disease? a case report - Ang Poh Thean, Charles; Awang, Mohd Shukrimi; Mor Japar Khan, Ed Simor Khan; Sabir Husin Athar, Satriya; Hao, Faun (Juniper Publishers, 2019)
Albers- Schonberg disease is an extremely rare genetically inherited disorder. Also known as Autosomal dominant Type II osteopetrosis, it is usually diagnosed incidentally. Due to the rarity of the disease, the condition is often missed and under- diagnosed. This is a case report of an eight- year old Malay girl that was diagnosed retrospectively after developing complications to the initial treatment given. Due to the underlying undiagnosed osteopetrosis rendering her prone for infections, a simple minimally invasive percutaneous K-wiring of her left tibia for a closed fracture was complicated with osteomyelitis causing significant morbidity. On retrospective review, her blood and radiographic investigations reveals low hemoglobin, raised alkaline phosphatase, rugger- jersey appearance of her spine radiograph, sclerosis over the base of skull and endo bones seen in her pelvic radiograph. She undergone wound debridement, and sequestrectomy a total of three times and was treated with intravenous antibiotics for six weeks and oral antibiotics for another six weeks. Despite the adequacy of surgical and antibiotic therapy, at one year follow up she still complains of on and off left proximal tibia pain significant enough to affect her daily activity. Therefore, it is important to make known the existence of this condition and double consider if surgical intervention is really needed or conservative approach will be a better option for primary treatment.